2020
DOI: 10.1007/s00415-020-09796-2
|View full text |Cite
|
Sign up to set email alerts
|

Retinal axonal degeneration in Niemann–Pick type C disease

Abstract: Objective Niemann-Pick disease type C1 (NPC1) is a rare autosomal-recessive lysosomal storage disorder presenting with a broad clinical spectrum ranging from a severe infantile-onset neurovisceral disorder to late-onset neurodegenerative disease. Optical coherence tomography (OCT) is established to detect retinal degeneration in vivo. We examined NPC1-patients (NPC1-P), clinically asymptomatic NPC1-mutation carriers (NPC1-MC), and healthy controls (HC) to (1) identify retinal degeneration in NPC1-disease and (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 46 publications
(51 reference statements)
1
15
0
Order By: Relevance
“…To the contrary we cannot support findings by Havla et al, who reported reduced volumes of macular NFL, as well as a thinner peripapillary RNFL, and combined GCL/IPL, compared to age- and sex-matched controls in their study. Of note, their patients exhibited reduced Snellen Visual Acuity Equivalent, while in our cohort almost all patients had normal visual acuity [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…To the contrary we cannot support findings by Havla et al, who reported reduced volumes of macular NFL, as well as a thinner peripapillary RNFL, and combined GCL/IPL, compared to age- and sex-matched controls in their study. Of note, their patients exhibited reduced Snellen Visual Acuity Equivalent, while in our cohort almost all patients had normal visual acuity [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…We will now specifically consider the mevalonate pathway in the RPE. While immunohistochemical analysis has shown the presence of HMGCR in human and murine RPE cells (61,80) imaging of the neural retina of NPC-1 patients has revealed significant thinning of the nerve fiber layer and axonal degeneration (112). Surprisingly, however, patients with lysosomal acid lipase (LAL) deficiency which results in accumulation of lysosomal cholesteryl esters do not exhibit retinopathies (113).…”
Section: Mevalonate Pathway Activity In the Retinal Pigmented Epithelmentioning
confidence: 99%
“…Previous studies investigated how CD affected NPC animal models and patients after chronic administration for weeks to months (Aqul et al, 2011;Berry-Kravis et al, 2018;Farmer et al, 2019;Fukaura et al, 2021;Ory et al, 2017;Palladino et al, 2015;Praggastis et al, 2015;Vite et al, 2015), but the immediate effects of CD on brain cells remain unknown despite growing interest in CD-based therapies for other neurodegenerative diseases (Coisne et al, 2016). Here, we addressed this fundamental question using the retina as accessible part of the CNS that is affected by NPC1 dysfunction in humans (Havla et al, 2020;Palmer et al, 1985) and in animal models (Claudepierre et al, 2010;Palladino et al, 2015;Phillips et al, 2008;Yan et al, 2014a). For drug administration, we chose intravitreal injections that enable direct delivery of molecules to the retina and subsequent monitoring of drug effects at defined time points (Del Amo et al, 2017).…”
Section: Introductionmentioning
confidence: 99%